Enzymatic studies in normal and repeat breeder buffaloes - DHABALE, R B; SHARMA, N C (The Indian Journal of Animal Reproduction, 2023)
The concentration of various serum enzymes in normal cyclic and repeat breeding buffaloes were studied. The mean levels ofGPT and GOT were 11 .04±0.96. 49.6±2.60 and 9.87±0.45. 53.22±1 .83 units/Lin normal cyclic and repeat breeding buffaloes. respectively, the differences were non-significant. Alkaline phosphatase and acid phosphatase levels were significantly higher in repeat breeding than normal cyclic buffaloes.